Answer:
see explanation
Step-by-step explanation:
Given
(a + b - 2)(a - b + 2)
Each term in the second factor is multiplied by each term in the first factor, that is
a(a - b + 2) + b(a - b + 2) - 2(a - b + 2) ← distribute the parenthesis
= a² - ab + 2a + ab - b² + 2b - 2a + 2b - 4 ← collect like terms
= a² - b² +4b - 4
answer: x=6
Step-by-step explanation:
move all terms that don't contain x to the right side and solve.
Answer:
=2x+4c+17
Step-by-step explanation:
(2x-3)+(4c+20)
=2x-3+4c+20
=2x+4c-3+20
=2x+4c+17
Answer:
12
Step-by-step explanation:
f(x)=x^+4x+2 First, let's evaluate when x=3, x=4 and x=5.
f(3) = 3²+4(3)+2 = 9 + 12 + 2 = 23
f(4) = 4²+4(4)+2 = 16 + 16 + 2 = 34
f(5) = 5²+4(5)+2 = 25 + 20 + 2 = 47
Now, let's find the rate of change.
34 - 23 = 11
47 - 34 = 13
Finally, the average rate of change.
(11 + 13) / 2 = 12
That flat horizontal line has zero slope. There's no change in y for every unit change in x.